2009
DOI: 10.1016/j.gene.2008.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal preferences for trans-splicing in Ciona intestinalis revealed by EST-based gene expression analysis

Abstract: Ciona intestinalis is a useful model organism to analyze chordate development and genetics. However, unlike vertebrates, it shares a unique mechanism called trans-splicing with lower eukaryotes. In the computational analysis of trans-splicing in C. intestinalis we report here, we discovered that although the amount of non-trans-spliced and trans-spliced genes is usually equivalent, the expression ratio between the two groups varies significantly with tissues and developmental stages. Among the seven tissues st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…These terms fell into several functionally interrelated themes featuring the plasma membrane/endomembrane system, transmembrane Ca 2+ transport, cell-cell signaling/secretion/ transmembrane signal transduction, membrane organization/ transport/endocytosis, cell adhesion, and cytoskeleton. In agreement with the results of Sierro et al (2009), we found the term ''protein transport'' overrepresented. However, we did not observe overrepresentation of terms related to mitochondria or to cell cycle, nor did Sierro and colleagues observe overrepresentation of membrane-or Ca…”
Section: Trans-splicing and Gene Functionsupporting
confidence: 90%
See 2 more Smart Citations
“…These terms fell into several functionally interrelated themes featuring the plasma membrane/endomembrane system, transmembrane Ca 2+ transport, cell-cell signaling/secretion/ transmembrane signal transduction, membrane organization/ transport/endocytosis, cell adhesion, and cytoskeleton. In agreement with the results of Sierro et al (2009), we found the term ''protein transport'' overrepresented. However, we did not observe overrepresentation of terms related to mitochondria or to cell cycle, nor did Sierro and colleagues observe overrepresentation of membrane-or Ca…”
Section: Trans-splicing and Gene Functionsupporting
confidence: 90%
“…Our previous study found no GO terms significantly overrepresented in a small sample (;330) of transspliced genes, but in a related sample of similar size Sierro et al (2009) reported that the terms ''mitochondrion,'' ''protein transport,'' and ''cell cycle'' were overrepresented in the trans-spliced gene class. A significant new finding of our current study was the identification of a large number of GO terms (>100) overrepresented among efficiently trans-spliced and frequently transspliced gene classes.…”
Section: Trans-splicing and Gene Functionmentioning
confidence: 78%
See 1 more Smart Citation